Impact of toothpaste use on the subgingival microbiome: a pilot randomized clinical trial - Margarita Iniesta; Viviane Vasconcelos; Florencia Laciar; Paula Matesanz; Mariano Sanz; David Herrera (BMC Oral Health)
Abstract Background The subgingival microbiome plays a key role in the gingivitis development, but the impact of toothbrushing with toothpaste on the subgingival microbial composition is not well understood. Therefore, this study aimed to evaluate the microbiological safety and subgingival impact of a toothpaste containing CPC and cymenol, compared to a fluoride-based toothpaste, and assessed overall subgingival microbiome changes after 6 weeks of routine toothbrushing in patients with gingival inflammation. Methods A 6-week randomized clinical trial was conducted in patients with gingival inflammation allocated to the use of either a toothpaste with cetylpyridinium chloride and cymenol or a toothpaste with sodium monofluorophosphate. Subgingival samples were collected at baseline and after 6 weeks and processed using high-throughput sequencing technology (Miseq®). Diversity metrics were calculated and the microbiome composition was analyzed using PERMANOVA, ANOSIM and PERMDISP. Results A total of 116 samples from 60 patients were analyzed. No significant changes in diversity were observed in either group after 6 weeks. Among taxa with > 1% abundance, the toothpaste with cetylpyridinium chloride and cymenol exhibited a higher reduction in Aggregatibacter (p = 0.023) and a significant decrease in Fusobacterium nucleatum (p = 0.030), while the toothpaste with sodium monofluorophosphate showed a significant increase in the phylum Firmicutes (p = 0.033). The relative abundance of Porphyromonas gingivalis, Prevotella intermedia and Tannerella forsythia were not affected by either toothpaste (p > 0.05). Conclusions The daily use of a CPC/cymenol toothpaste was microbiologically safe, with no negative effects on the composition of the subgingival microbiome in patients with gingival inflammation, when compared to a fluoride-based toothpaste. The overall composition of the subgingival microbiome was not significantly affected by the daily use of either toothpaste after 6 weeks. In both groups, the observed changes affected mainly the low-abundance taxa. Trial registration Registration Number: ISRCTN17497809; Registration Date: 12/07/2023 (ISRCTN.org).